2011
DOI: 10.2298/tsci100614088e
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and emission characteristics of a diesel engine fuelled with jatropha and diesel oil blends

Abstract: The depletion of oil resources as well as the stringent environmental regulations has led to the development of alternate energy sources. In this work the combustion, performance and emission characteristics of a single cylinder diesel engine when fuelled with blends of jatropha and diesel oil are evaluated. Experiments were conducted with different blends of jatropha oil and diesel at various loads. The peak pressures of all the blends at full load are slightly lower than the base diesel. There is an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…Also the Y2JE15 emulsion practiced a fall in the brake thermal efficiency by 11.5%. The increase in brake thermal efficiency of JE10, JE15 and Y2JE10 are the development of the combustion process on report of better oxygen content in the different fuels [11]. In case of Y2JE15 emulsions, thermal efficiency is fall down with minimum calorific values of the fuel blends and poor mixture creation.…”
Section: Performance Analysismentioning
confidence: 99%
“…Also the Y2JE15 emulsion practiced a fall in the brake thermal efficiency by 11.5%. The increase in brake thermal efficiency of JE10, JE15 and Y2JE10 are the development of the combustion process on report of better oxygen content in the different fuels [11]. In case of Y2JE15 emulsions, thermal efficiency is fall down with minimum calorific values of the fuel blends and poor mixture creation.…”
Section: Performance Analysismentioning
confidence: 99%
“…Fig. 6 shows the variation of NOx with respect to brake power [12]. At higher power output conditions, due to higher peak and exhaust temperatures the NOx values are relatively higher compared to low power output conditions.…”
Section: B Emission Characteristicsmentioning
confidence: 99%
“…This biodiesel has a high cetane number compared to diesel, less sulfur and contains more oxygen, almost 10% oxygen by weight. These characteristics are environmentally friendly and can reduce the hydrocarbon (HC), carbon monoxide (CO), and PM emissions in the exhaust gas [10][11][12][13][14][15]. For these reasons, different studies have been conducted on biodiesel blended with diesel showing that emission concentration (CO, CO 2 , HC, PM, NOx) varies and it all depends on the source of the biodiesel and the engine combustion system.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of prepared waste frying oil (WFO) was compared with diesel using the four-cylinder compression ignition engine of the Land Rover TDI 110 and the results showed that for CO and NOx the emissions are lower than those for petroleumbased diesel [11,12]. Other than that, preheated crude palm oil (CPO) fuel in the test engine produced higher NOx emissions compared with diesel [16][17][18].…”
Section: Introductionmentioning
confidence: 99%